British culture - Christopher, David (Routledge, 2015)
Include index; Timeline -- The social and cultural context -- Language in culture -- Cyberculture -- Newspapers, magazines and journalism -- Literature -- Theatre -- Cinema -- Television and radio -- Art and architecture -- Popular music and fashion -- Sport -- Heritage and festivals